Pedicled neurocutaneous anterolateral thigh flap for groin reconstruction – A case report. Issue 5 (8th April 2019) - Gentileschi, Stefano; Albanese, Roberta; Servillo, Maria; Pino, Valentina; Stefanizzi, Gianluigi; Garganese, Giorgia; Scambia, Giovanni; Salgarello, Marzia
Abstract: Several different flaps based on the feeding vessels of sensitive nerves have been described in the limbs. This article reports the case of a neurocutaneous flap based on the lateral femoral cutaneous nerve (LFCN), employed for reconstruction of an inguinal defect. A 61‐years‐old female patient had undergone vulvectomy and bilateral inguinal lymphadenectomy for vulvar cancer with postoperative left groin wound breakdown. After a 3 weeks negative pressure therapy course, she presented a 10 × 4 cm skin and subcutaneous defect with undermined edges in the left inguinal area. Reconstruction with 14 × 6 cm pedicled left anterolateral thigh flap was planned. After the dissection of the vascular pedicle and of the sensitive nerve, complete thrombosis of both the veins and arterial spasm of perforating pedicle was detected. As the flap color was good, and slow marginal bleeding was present, we inspected the small vessels surrounding the nerve that were pulsating. To confirm the vascularization coming from the neural pedicle, we clamped the perforator and performed intraoperative indocyanine green (ICG) fluorescence angiography that showed a good fluorescence of the flap with a proximal to distal pattern of progression. The flap was transferred on the neural pedicle, survived completely, and wounds healed normally. Three months after surgery, the patient underwent radiotherapy, with uneventful course. In her last follow‐up, 2 years after surgery, patient was free of disease and the flap showed normal scarring. This is the first case reported of a pedicled neurocutaneous flap based on the LFCN, indicating that in case of unsuitable perforators it could be an alternative pedicle.